2018
DOI: 10.4174/astr.2018.95.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Postcholecystectomy syndrome: symptom clusters after laparoscopic cholecystectomy

Abstract: PurposePostcholecystectomy syndrome (PCS) is characterized by abdominal symptoms following gallbladder removal. However, there is no consensus for the definition or treatment for PCS. The purpose of this study was to define PCS among various symptoms after laparoscopic cholecystectomy, and to identify risk factors affecting PCS.MethodsThis study was conducted at Dongguk University Ilsan Hospital and Chung-Ang University Hospital (2012–2013). Outcomes were assessed using European Organization for Research and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“… 18 The other RCT was to investigate the effect of Rowachol on post-Laparoscopic cholecystectomy pain, however, the authors also assess symptom clusters including diarrhoea, once again meriting including into the study. 10 The studies and data obtained are shown in table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 The other RCT was to investigate the effect of Rowachol on post-Laparoscopic cholecystectomy pain, however, the authors also assess symptom clusters including diarrhoea, once again meriting including into the study. 10 The studies and data obtained are shown in table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 39 Talseth et al study found that PCD was more common in patients having cholecystectomy for biliary colic, while Manriquez et al 22 asserted that it was more common in patients having cholecystectomy for asymptomatic cholelithiasis. 22 41 On the other hand, Kim et al 10 identified no predictive factors including age, BMI, sex, American society of Anaesthetists score, preoperative Endoscopic retrograde cholangiopancreatography (ERCP), comorbidities, difficult laparoscopic cholecystectomy, open conversion or pathology. 10 Wanjura et al 42 found that several factors were predictive of worse gastrointestinal symptoms after cholecystectomy, including female gender, CBD stones or pancreatitis and gallstone pain as an indication for surgery, however, did not particularly relate this to diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…Postcholecystectomy syndrome (PCS) is a symptom complex that contains functional and organic disorders of the major duodenal papilla (MDP) [1,2]. The most co mmon causes of PCS, both after cholecystectomy (CE) performed by the «open» method, and after laparoscopic CE, are: stones forgotten or moved during intervention in the choledochus from the gallbladder or cystic duct [3], recurrent choledocholithiasis (mainly after preliminary endoscopic manipulations with stone extraction attempts) [4,5], MDP restenosis after endoscopic papillosphincterotomy (EPST) [6], blind pouch syndrome, long vesical stump syndrome, biliary fistula, tubular stenosis of the distal choledochus due to chronic indurative pancreatitis, reflux cholangitis due to total EPST and wide choledochoduodenoanastomosis, electrical injury of the biliary tract [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that the factors influencing the recurrence of calculi in different studies vary, which may be an important reason for the various findings. Some physicians believe that the high recurrence rate of gallstones after gallstone-conserving surgery is mainly due to residual gallstones, mucosal injury and bleeding during gallstone removal 5 .…”
Section: Introductionmentioning
confidence: 99%